A biologically inspired two-species exclusion model: effects of RNA polymerase motor traffic on simultaneous DNA replication. (5th April 2018) - Ghosh, Soumendu; Mishra, Bhavya; Patra, Shubhadeep; Schadschneider, Andreas; Chowdhury, Debashish
Abstract: We introduce a two-species exclusion model to describe the key features of the conflict between the RNA polymerase (RNAP) motor traffic, engaged in the transcription of a segment of DNA, concomitant with the progress of two DNA replication forks on the same DNA segment. One of the species of particles ( P ) represents RNAP motors while the other ( R ) represents the replication forks. Motivated by the biological phenomena that this model is intended to capture, a maximum of two R particles only are allowed to enter the lattice from two opposite ends whereas the unrestricted number of P particles constitutes a totally asymmetric simple exclusion process (TASEP) in a segment in the middle of the lattice. The model captures three distinct pathways for resolving the co-directional as well as head-on collision between the P and R particles. Using Monte Carlo simulations and heuristic analytical arguments that combine exact results for the TASEP with mean-field approximations, we predict the possible outcomes of the conflict between the traffic of RNAP motors ( P particles engaged in transcription) and the replication forks ( R particles). In principle, the model can be adapted to experimental conditions to account for the data quantitatively.